Flavestin K, An Isoprenylated Stilbene from the Leaves of Macaranga recurvata Gage - Tjitjik Srie Tjahjandarie*, .- (Korean Society of Pharmacognosy, 2019)
A new isoprenylated stilbene, flavestinK (1) together with two known isoprenylated stilbenes, flavestin B (2), flavestin G (3), and two isoprenilated flavanones, 4-O-methyl-8-isoprenylnaringenin (4) and 8- isoprenyl-5,7-dihydroxyflavanone (5) were isolated from the leaves of Macaranga recurvata Gage. All of the structures have been determined based on HRESIMS, 1D and 2D NMR spectral data. All of the isolated compounds were evaluated for their cytotoxicity against three human cancer cells (HeLa, T47D and WiDr). Compound 1 showed higher activity than doxorubicin against HeLa cells with IC50 value of 13.1 µg/mL